STREAMLINING LABORATORY INTEGRATION IN HEALTHCARE DELIVERY: A REVIEW OF COLLABORATIVE CARE MODELS - Esam Abdullah Mohammed Alaamri, ⁠Hadeel Hassan Almadkhly,⁠ Ahmed Ali Awaji Dighriri,⁠ Mohammed Abdu Ammash Khobrany,⁠ Mishaan Mohamed Aljihany, ⁠Mustafa Ahmed Edrees Hamzi,⁠ Turki Ali Saad Alharthi, ⁠Yaser Afandi Hamad Hakami,⁠ ,; Essa Awad Hayyan Alanazi, ⁠Ahmad Saeed Ali Alahmari,⁠ Nawaf Ali Atiah Khubrani,⁠ Aishah Ali Ali Sharahili,⁠ Nader Munaji Abdu Suwayyid, Abdulrahman Mohammed Refaei, (Chelonian Research Foundation, 2022)
The convergence of technology and healthcare has sparked significant changes, especially in the field of medical laboratory testing. This article provides insight into the historical development of laboratory procedures and highlights the crucial significance of contemporary technology advancements, including automation, digital imaging, data analytics, and integrated electronic health systems. The transformation is characterized by the use of automation, allowing for efficient processing of a large number of samples; digital imaging, providing unparalleled accuracy in sample analysis; and powerful data analytics that can identify complex patterns. Adding to the improvement of this environment is the rise of networked electronic health systems, which facilitate the rapid sharing of diagnostic results across different medical organizations. The innovations have unquestionably improved the accuracy of diagnoses and sped up patient treatment, hence minimizing the anxiety caused by extended waiting periods. Nevertheless, this era of technical advancement is not without its difficulties. Emerging difficulties include worries about data security, the possibility of system faults, and the need for continuous staff training. As we imagine a future where healthcare and technology are closely connected, it is crucial to tackle these difficulties. Our unrelenting commitment to medical excellence is centered upon the synthesis of adaptive techniques and these technologies. Keywords: Healthcare, Technology, laboratory, Automation, Digital imaging, Data analytics, Diagnostic results, Data privacy, System faults.